Quality of Service in metropolitan area networks - Kang, Jen Wee. (2008)
In this research, the Optical Burst Switching (OBS) is looked into to study the possibilities of implementing Quality of Service (QoS) on a Metropolitan network. In literature, equipment such as Fiber Delay Lines and Wavelength Converters are utilized to provide performance enhancement to the network. However, such equipment is currently impractical and expensive.